Getting out of the vicious traffic circle: attemps at restructuring the cultural ambience of the automobile throughout the 20th century - Mikael Hård; Andreas Knie (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2000)
For years, alternative vehicle and propulsion concepts have had a very difficult time catching on, even though technicians and engineers have repeatedly pointed out that the design quality of electric propulsion systems or other novel vehicle concepts is available and feasible. Often enough, this state of affairs allowed free rein for various conspiracy theories, in which extraneous issues were made responsible for the lack of technological breakthrough. This paper agues, however, that innovation research has itself focused too narrowly on the process of the establishment of new products. On the basis of five case examples —the implementation of diesel engine propulsion for street vehicles; the EV1, the first electrically propelled standard car by General Motors; Ford's prototype electric car study “Pivco”; the NSU Wankel engine; and the “Smart” car manufactured by DaimlerChrysler — an attempt is made to develop a comprehensive understanding of innovation processes which does not stop at the “technical invention” of a device. The thesis is that a new device requires a relevant cultural ambience, which must be more or less invented alongside it in multiple dimensions. Technical-constructive work is thus only one part of a successful innovation process; parallel to this, complementary measures must be taken with regard to the overall sectoral environment, law-making, user perceptions and attributions of meaning, as well as the cultural appropriation of a given device. Without the appropriate “adaptive measures”, even the most interesting technical projects runs the risk of sinking onto oblivion for lack of relevance. – – Alternative Antriebs- und Fahrzeugkonzepte tun sich in der Durchsetzung schon seit Jahren sehr schwer, obwohl immer wieder von Technikern und Ingenieuren darauf verwiesen wird, dass die konstruktive Qualität von elektrischen Antriebssystemen oder anderen neuartigen Fahrzeugkonzepten vorhanden sei. Oft genug konnten daher Verschwörungstheorien Raum greifen, in denen sachfremde Tatbestände für die fehlenden technischen Durchbrüche verantwortlich gemacht wurden. Im vorliegenden Beitrag wird argumentiert, dass die Innovationsforschung selbst einen zu engen Blick auf die Prozesse der Etablierung neuer Produkte eingenommen hat. Anhand von fünf Fallbeispielen, der Durchsetzung des dieselmotorischen Antriebes für Strassenfahrzeuge, des EV1, des ersten elektrisch betriebenen Serienfahrzeuges von General Motors, der Konzeptstudie Pivco, einem Elektroautomobilprojekt des Ford-Konzerns, des NSU-Wankelmotors sowie des neuartigen Fahrzeugkonzeptes Smart wird hingegen versucht, ein umfassendes Verständnis von Innovationsprozessen zu entwickeln, das nicht bei der technischen Erfindung eines Gerätes halt macht. Die These ist, dass neue Geräte zur Durchsetzung am Markt auch einen entsprechenden Funktionsraum benötigen (cultural ambience), der mehrdimensional sozusagen immer gleich miterfunden werden muss. Die technisch-konstruktive Arbeit ist daher nur ein Teilbereich eines erfolgreichen Innovationsprozesses. Parallel müssen weitere Vorkehrungen im Branchenumfeld, bei der Gesetzgebung, bei den Nutzerperzeptionen und Bedeutungszuschreibungen sowie den kulturellen Aneignungsweisen vorgenommen werden. Ohne die entsprechenden Anpassungsmassnahmen droht auch den interessantesten technischen Projekten aus Mangel an Relevanz die Bedeutungslosigkeit.
Keywords: 330; Innovationsdiffusion; Wirtschaftssoziologie; Welt; Kraftfahrzeugmotor; Kraftfahrzeugtechnik